2015
DOI: 10.1515/quageo-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Soil Determinants of Forest Cover Changes in Świętokrzyski National Park and Its Buffer Zone in the last 200 Years

Abstract: The research described in the paper utilized GIS methods and comparative cartography in order to analyze changes in forest cover in the period 1800-2011 in the Świętokrzyski National Park (76.26 km²) and its buffer zone (207.86 km²). The research was done for predefined elevation intervals, slope gradients, and genetic soil types. Source materials included historical maps as well as a digital elevation model. Changes in forest cover were noted in spatial and temporal terms and were usually linked to morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Similar patterns were found in the loess areas of China (Fu et al 2006). The role of slope gradient and elevation above sea level, on the spatial distribution of forests, was also noted in research conducted in central Poland (Ciupa et al 2015), Germany (Hietel et al 2004) and the Czech Republic (Opršal et al 2013). Wulf et al (2010) found a clear relationship between forest cover changes and soils in NE Germany.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Similar patterns were found in the loess areas of China (Fu et al 2006). The role of slope gradient and elevation above sea level, on the spatial distribution of forests, was also noted in research conducted in central Poland (Ciupa et al 2015), Germany (Hietel et al 2004) and the Czech Republic (Opršal et al 2013). Wulf et al (2010) found a clear relationship between forest cover changes and soils in NE Germany.…”
Section: Discussionmentioning
confidence: 69%
“…The relation of forest cover changes to environmental variables is important from the point of view of soil and gully erosion, risk of floods, and transfer of pollutants in the environment. Studies on the role of natural factors in changes to forest cover conducted in Poland so far have focused on mountain areas (Kozak et al 2007a, b;Ciupa et al 2015). Within these regions intense deforestation was observed in the nineteenth and twentieth century while in its second half a new process started-reforestation, as a result of land abandonment.…”
Section: Introductionmentioning
confidence: 99%
“…An effect of soil properties on forest cover was shown for the Central European lowlands [36,42,43], where more fertile soils were usually deforested. Similarly, Ciupa et al [70] found a higher deforestation rate on soil suitable for agriculture in the Świętokrzyskie Mts, however this was not tested statistically. We assume that in the studied region a relatively complex land relief caused the patchy distribution of forest and agricultural lands (Fig.…”
Section: Local Drivers Of Changes In Forest Covermentioning
confidence: 94%
“…The average forest cover of eighteenthcentury Europe was 42%, the forest cover in Carinthia (Alps) was 41%, while in Transylvania (Carpathians) it was 48% [4,69]. During the same period, the percentage of forest cover in the Karkonosze Mts (Sudety) was 45% [34] and, at the very beginning of the nineteenth century, it was 41% in the Świętokrzyskie Mts [70]. The rather low forest cover of the study area was attributed to the relatively low altitude of the region, which increases its agricultural potential and the density of the human population.…”
Section: Forest Cover and Global Drivers Of Changes In Forest Covermentioning
confidence: 99%